Power Amplification for Jumping Soft Robots Actuated by Artificial Muscles - Fernandes Minori, Adriane; Jadhav, Saurabh; Chen, Haojin; Fong, Samantha; Tolley, Michael T. (Frontiers in Robotics and AI, 2022)
Robots composed of soft materials can passively adapt to constrained environments and mitigate damage due to impact. Given these features, jumping has been explored as a mode of locomotion for soft robots. However, for mesoscale jumping robots, lightweight and compact actuation are required. Previous work focused on systems powered by fluids, combustion, smart materials, electromagnetic, or electrostatic motors, which require one or more of the following: large rigid components, external power supplies, components of specific, pre-defined sizes, or fast actuation. In this work, we propose an approach to design and fabricate an electrically powered soft amplification mechanism to enable untethered mesoscale systems with continuously tunable performance. We used the tunable geometry of a liquid crystal elastomer actuator, an elastic hemispherical shell, and a pouch motor for active latching to achieve rapid motions for jumping despite the slow contraction rate of the actuator. Our system amplified the power output of the LCE actuator by a factor of 8.12 x 10^3 with a specific power of 26.4 W/Kg and jumped to a height of 55.6 mm (with a 30 g payload). This work enables future explorations for electrically untethered soft systems capable of rapid motions (e.g., jumping).